2021
DOI: 10.1039/d1sc04430c
|View full text |Cite
|
Sign up to set email alerts
|

FeII4L4 tetrahedron binds and aggregates DNA G-quadruplexes

Abstract: Since the discovery of the G-quadruplex (G4) structure in telomeres in 1980s, studies have established the role it plays in various biological processes. Here we report binding between DNA G4...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In addition to these Fe(II) cage systems binding small biomolecules within their cavities they have also been shown to interact with larger biomolecules such as DNA and proteins. Nitschke, Keyers and co‐workers showed that a water soluble Fe II 4 L 4 tetrahedral cage can bind and aggregate G‐quadruplex DNA [44] . Similar binding and/or aggregation of various different DNA, RNA and peptide constructs has also been observed with smaller Fe(II), Ni(II), and Co(III) M 2 L 3 MSAs [45]…”
Section: Molecular Recognitionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to these Fe(II) cage systems binding small biomolecules within their cavities they have also been shown to interact with larger biomolecules such as DNA and proteins. Nitschke, Keyers and co‐workers showed that a water soluble Fe II 4 L 4 tetrahedral cage can bind and aggregate G‐quadruplex DNA [44] . Similar binding and/or aggregation of various different DNA, RNA and peptide constructs has also been observed with smaller Fe(II), Ni(II), and Co(III) M 2 L 3 MSAs [45]…”
Section: Molecular Recognitionmentioning
confidence: 96%
“…Nitschke, Keyers and co-workers showed that a water soluble Fe II 4 L 4 tetrahedral cage can bind and aggregate G-quadruplex DNA. [44] Similar binding and/or aggregation of various different Aston is completing a Master's degree at the University of Otago under the supervision of Professor James Crowley, working on heterometallic low-symmetry cages. He is interested in selfassembly and molecular recognition.…”
Section: Molecular Recognitionmentioning
confidence: 99%
“…15 As we all know, the double-helix structures of DNA molecules in living organisms are also formed by the perfect matching of hydrogen bonds between base units. 16 This stable binding mode provides inspiration to design supramolecular interactions between host and guest molecules. Therefore, the introduction of multifarious functionality groups as hydrogen donors modified on the organic linker and thus into the host cages as interaction sites is a feasible approach to enhance the binding ability toward specific guests with complementary groups.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonds, considered the key and predominant weak interactions, widely exist in biological and chemical systems and also play a significant role in supramolecular assembly . As we all know, the double-helix structures of DNA molecules in living organisms are also formed by the perfect matching of hydrogen bonds between base units . This stable binding mode provides inspiration to design supramolecular interactions between host and guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Many promising applications for individual cages have now been investigated [34][35][36][37]. These include applications for sequestering a wide range of both ions and molecules [38][39][40][41]; for molecule and ion sensing [23,[42][43][44][45][46][47][48][49][50][51][52][53][54][55]; for the stabilisation of reactive species [56,57]; for catalysis where the cage acts as a "reaction vessel" in which, for example, the proximity of the reactants (amongst other influences) act as a driver for promoting enhanced reaction rates [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]; as well as for use in biochemical applications [76,77] that include MRI imaging [78], photodynamic therapy …”
Section: Introductionmentioning
confidence: 99%